THE EFFECT OF INDEPENDENCE, PROFESSIONALISM AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF INTERNAL AUDITORS - Siti Maria Wardayati; Wasito Wasito; Alfi Arif; Septarina Prita Dania Sofianti; Nining Ika Wahyuni; Arif Hidayatullah (UNEJ e-Proceeding, 2022)
This study aims to analyze the effect of the relationship between Internal Auditor Performance. The variables of the internal auditor's performance consist of Organizational Culture, Independence and Professional Ethics. Based on previous research, there is a Research Gap in the results of the research provided so that researchers are interested in re-testing by including the professionalism variable. The novelty of this study from previous researchers lies in the use of a variable, namely professionalism that affects the performance of BPKP auditors. This research was conducted using a survey method through a questionnaire. Sampling in this study using random sampling method. The sample in this study used as respondents were all BPKP auditors from functional positions as implementing auditors, advanced implementing auditors, supervisory auditors, junior auditors, first auditors, middle auditors, middle auditors, main auditors and middle auditors as supervisory coordinators, totaling approximately 100 respondents. The data that has been collected is then analyzed using Multiple Regression Analysis. The results of this study indicates that independence has an effect on BPKP Auditor Performance. The relationship shown by the regression coefficient is positive, meaning that the higher the independence, the higher the performance of the BPKP Auditor will be. Auditor Professionalism has no effect on BPKP Auditor Performance, meaning that the level of auditor professionalism will not affect BPKP auditor performance. Organizational Culture has no effect on the Performance of BPKP Auditors, meaning that the good or bad of Organizational Culture will not affect the performance of the auditors. Keywords: Organizational Culture, Independence, Professionalism, and Performance.